The Effect of Tax Planning, Accrual Basis, Company Growth, and Operating Cash Flow on Profit Management - Wahid Akbar Basudani; Wiharso, Gani (Universitas Pamulang, 2025)
The objective of this research is to analyze the impact of tax planning, accrual basis, growth, and operating cash flow on earnings management. This research is an associative quantitative research. The data used are in the form of secondary data of the audited financial report and published by each manufacturing company within the consumer goods industry listed on the Indonesia Stock Exchange (IDX) for the period 2015– 2019. The sampling technique in this study uses purposive sampling technique, from the 56 company population determined in the consumer goods industry listed on the Indonesia Stock Exchange obtained a sample of 16 companies for 5 years so that the total sampled is 80 samples. The data analysis in this research uses panel data regression which is processed with the help of the Eviews 9 program. The results of this study indicate that tax planning, accrual basis, growth, and operating cash flow simultaneously affect earnings management. Partially, tax planning has no effect on earnings management. The accrual basis has a positive effect on earnings management. Growth has no effect on earnings management. Operating cash flow has a negative effect on earnings management.